The power of dignity : how transforming justice can heal our communities - Pratt, Victoria (Seal Press, 2022)
"Failed, biased, hostile: these are the words many use to describe the condition of the U.S. court system today. In The Power of Dignity, acclaimed criminal justice reformer Victoria Pratt offers a path forward to restoring public trust in the courts: procedural justice, the simple idea that people will obey the law if they are treated with dignity, respect, and fairness by the justice system. Growing up as the daughter of an African-American sanitation worker and a Dominican beauty salon owner, Victoria Pratt learned one simple lesson at a young age: treat everyone with respect, no matter what they look like or where they come from. Carrying that with her as she became the Chief Judge of the Newark Municipal Court, she found that showing respect not only changed lives, it transformed the way justice was done in her community. Drawing on years of experience, Pratt breaks down how her reforms can be implemented to build trust in the rule of law. Too often, people seemed to be imprisoned for being Black, brown, poor, or mentally ill-when she knew, none of these things were crimes. Through her stories, research, and insights, she reveals how leaders can better address each defendant's potential, approach them as a whole person, connect them with community resources, and restore them back into society. She explains the reasoning behind strategies she's pioneered, such as assigning essays to defendants, offering alternatives to jailtime, and connecting people with the support they need to stay out of the court system for good. And we can all learn from her lessons in empathy and compassion to shift toward a more humane form of community leadership. With a foreword from Senator Cory Booker, The Power of Dignity will shake readers to their core, and then compel them to reshape our neighborhoods and our nation into a truly just society. When judges treat offenders with respect and decency, they respond in turn. When we allow everyone a second chance to contribute to our communities, they become stronger. That's the power of dignity"--